Do national well-being scores capture nations' ecological resilience? Evidence for 124 countries - Heinz Welsch (University of Oldenburg, Department of Economics, 2024)
Resilience is the ability of an entity to manage a destabilizing shock or rise in pressure. The recently published State Resilience Index (SRI) includes ecological resilience along with several other "pillars" of state resilience. Given that indicators of subjective well-being (SWB) are increasingly accepted as a measure of national performance and as a standard for evaluating public policy, this paper investigates whether national SWB scores capture the ecological resilience dimension of national performance. Regression analysis of data for 124 countries reveals that SWB is significantly positively related to the ecological pillar of state resilience as well as some of its subpillars, but not others. In multivariate regressions, significant sub-pillars of ecological resilience are agricultural productivity, low levels of pollution, and freshwater availability, but not ecosystem health, long-term climate stability and biodiversity. The evidence is taken to suggest that SWB captures the more tangible aspects of the state of the environment rather than latent ecological threats whose full consequences will mainly be felt in the future. To capture latent ecological threats, SWB-based performance measures will therefore have to be complemented by more forward-looking indicators of ecological resilience.
Keywords: Q20; Q50; I31; 330; ecological resilience; subjective well-being; national performance; environmental threat; forward-looking